A history of the fens of South Lincolnshire, being a description of the rivers Witham and Welland and their estuary, and an account of the reclamation, drainage, and enclosure of the fens adjacent thereto - Wheeler, W. H. 1832-1915 (J.M. Newcomb, 1894)
This title starts with the early history of the Fens and moves through the origin and constitution of the Court of Sewers, on to all the different parishes and districts, and finishes with more general chapters on geology and water supply, natural history, etc. There are also 8 appendices.